Emerging Heat Risk in South Florida: Temperature Trends, Hospitalizations, and Lessons from India to Inform Early Public Health Adaptation Strategies - Luis Armas; Noel Singh Dias; Sarah Rodriguez; Brenda Barreto; Jessy Dévieux (International Journal of Environmental Research and Public Health, 2026)
Rising global temperatures are intensifying the frequency, duration, and severity of extreme heat events, posing a growing public health burden worldwide. Heat exposure is increasingly recognized as a major contributor to morbidity and mortality, particularly in regions with high baseline temperatures and large vulnerable populations. This study examines long-term temperature trends and their unadjusted association with heat-related health outcomes across major cities in India and counties across South Florida from 2005 to 2023. Major cities in India are used as a high-burden reference setting with established heat adaptation strategies, providing a framework for understanding how similar risks are emerging in South Florida. This comparison is conceptual, given differences in data structure and availability across regions. A retrospective ecological analysis was conducted using secondary data. Climate variables included annual mean temperature, while health outcomes focused on age-adjusted heat-related hospitalization rates. Temporal trends were assessed using graphical analysis and exploratory statistical analysis to inform early public health adaptation strategies. South Florida exhibited a warming rate of approximately +0.0265 °F/year compared to +0.0230 °F/year in major Indian cities, indicating a slightly faster pace of temperature increase in the subtropical region. County-level regression models in South Florida showed strong model fit, with R2 values ranging from 0.356 to 0.615 (all p < 0.01), indicating a consistent positive relationship between summer mean temperature and heat-related hospitalization rates. Miami-Dade County demonstrated the strongest association (R2 = 0.615), while Palm Beach County showed greater variability despite maintaining a statistically significant relationship (p = 0.007). Across all counties, heat-related hospitalization trends increased over time in parallel with rising temperatures. These findings, even though exploratory and unadjusted, position South Florida as an emerging high-risk region, where increasing temperature trends are beginning to mirror patterns observed in historically heat-burdened settings such as India. Lessons from India’s implementation of heat action plans, early warning systems, and community-level interventions provide a framework for strengthening climate adaptation strategies in South Florida.